EFEKTIVITAS INOKULASI TRICHODERMA DAN MIKORIZA TERHADAP PERTUMBUHAN DAN PRODUKSI BIOMASSA AWAL REGROWTH PERTAMA ALFALFA (Medicago sativa L.) DI LAHAN MARJINAL: EFFECTIVENESS OF TRICHODERMA AND MYCORRHIZA INOCULATION ON GROWTH AND BIOMASS PRODUCTION OF EARLY FIRST REGROWTH OF ALFALFA (Medicago sativa L.) IN MARGINAL LAND - Muhammad Husein; Ali Mursyid Wahyu Mulyono; Ludfia Windyasmara; Salnan Irba Novaela Samur (Tropical Animal Science, 2026)
This experiment aims to evaluate the effectiveness of inoculation and synergy of Arbuscular Mycorrhizal Fungi (AMF) and Trichoderma harzianum on the growth, productivity, and effectiveness of inoculation of Alfalfa (Medicago sativa L.) forage in marginal land in the early phase of the first regrowth. This experiment used biological agents, mycorrhizae, and Trichoderma. This study used a completely randomised design with a one-way pattern consisting of four treatments and five replications, namely T0: without inoculation; T1: Mycorrhizae 300 spores/polybag; T2: Trichoderma 5 grams, 1 × 106 spores/gram; T3: Combination of Mycorrhizae 300 spores/polybag and Trichoderma 5 grams, 1 × 106 spores/gram. Data were analysed using Analysis of Variance (ANOVA). The results showed that AMF inoculation in treatment T1 had a significant effect (p <0.05) on plant length (cm), number of branches (strands per branch), fresh biomass of the canopy and the effectiveness of inoculation. Treatments T2 and T3 were not significantly different from T0 (p>0.05) regarding plant length, but the number of branches differed. T2 and T3 showed significant differences (p<0.05), which were higher than the control, but not with the results of fresh shoot biomass and inoculation effectiveness. T2 gave insignificant results and was not better than treatments T1 and T3. Mycorrhizal inoculation T1 positively responded to plant growth, fresh shoot biomass and inoculation effectiveness under drought stress, although the combination treatment T3 also provided good feedback.